THE ROLE OF MOTIVATION IN IMPROVING TEACHER PERFORMANCE - Al-Fatih, Muhammad; Hayati, Fitri (Indikator Pendidikan Indonesia, 2023)
Teachers have a very strategic role in ensuring the success of learning and improving the quality of education. In order for the teacher's duties and responsibilities to be carried out properly, a teacher must have the expertise, desire, and effort in teaching and learning activities which include planning, organizing, implementing, and evaluating educational outcomes. Teachers are expected to have great motivation so that the work they carry out can run optimally. If a teacher has the positive motivation, he will show attention, attention, and willingness to participate in carrying out tasks or activities. The purpose of this research is to examine the role of motivation in improving teacher performance to produce effective and optimal learning. The literature study method was used in this study to obtain information and data about the role of motivation in improving teacher performance.